PS-BPB08-4: IMPAIRED TCA CYCLE METABOLISM IN DIABETIC NEPHROPATHY IS LINKED TO ALBUMINURIA AND KIDNEY INJURY. (January 2023) - Azushima, Kengo; Kovalik, Jean Paul; Yamaji, Takahiro; Gurley, Susan Bailey; Coffman, Thomas Myron
Abstract : Objective: Recent work has highlighted potential contributions of impaired renal energy metabolism, including mitochondrial dysfunction and altered fatty acid metabolism, in chronic kidney diseases including diabetic nephropathy (DN). However, causal connections between specific metabolic abnormalities and pathophysiology of DN have been difficult to establish. Here, we approach this question using a mouse model recapitulating characteristic features of human DN and a targeted metabolomics platform designed to assess key metabolic pathways involving amino acids, fatty acids, glycolysis and the TCA cycle. Design and method: We generated a mouse model of DN with underlying activation of the renin-angiotensin system (RAS) by a renin transgene ( R ) driven by the albumin promoter on the Akita background of type I diabetes ( A ). We have shown that on a susceptible 129/Sv background, Akita-ReninTg ( AR ) mice exhibit cardinal characteristics of human DN including high-grade albuminuria and glomerulosclerosis, whereas AR mice on a C57BL/6 background do not develop DN. To assess the impact of genetic background on energy metabolism in DN, kidneys from 24-week-old male AR mice on both backgrounds were evaluated by the targeted metabolome analysis. To further distinguish the impact of RAS activation on relevant pathways associated with kidney disease development, 12-week-old male 129/Sv AR mice were treated with the angiotensin receptor blocker (ARB) losartan 10 mg/kg/day for 12 weeks. 24-hour urine samples were collected in metabolic cages and urine albumin levels were measured by EIA. Kidneys from age-matched parental 129/Sv and C57BL/6 wild-type mice were analyzed as controls. Results: A distinct metabolic profile was observed in kidneys of DN-susceptible 129/Sv AR mice including reduced levels of C2 acetyl-carnitine that reflect a deficiency in acetyl-CoA, perturbations of TCA cycle intermediates and increased lactate levels. In addition, levels of phosphorylated-AMPK were reduced. These metabolic changes were absent in DN-resistant C57BL/6 AR mice. Treatment of 129/Sv AR mice with the ARB dramatically reduced albuminuria (906 ± 169 vs 193 ± 42 μg/day, p < 0.01) and attenuated kidney pathology while restoring levels of C2 acetyl-carnitine, TCA intermediates, lactate and phosphorylated-AMPK toward normal. ARB treatment also increased kidney ATP content. In 129/Sv mice, there were statistically significant correlations between albuminuria and kidney levels of lactate, acetyl-carnitine, citrate and succinate. Conclusions: Thus, there is a distinct profile of impaired energy metabolism associated with DN susceptibility that is attenuated by RAS blockade. Impaired TCA cycle function and coincident increases in lactate are linked to albuminuria in mice with DN, and may contribute to kidney injury.